Partisipasi Kelompok Sadar Wisata Dalam Pengembangan Desa Wisata Meat Kecamatan Tampahan Kabupaten Toba - Dela Wardani Pardede; Yulia K.S Sitepu; Robert Juni Tua Sitio; Mery Silalahi; Rusmauli Simbolon (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This study aimstodetermine the participation of pokdarwis in the development of the Meat Tourism Village and which parties are involved with the pokdarwis in the development of the Meat Tourism Village. This study uses qualitative research methods with descriptive methods and data collection techniques through observation and interviews with 10 informants. The results of this study depict that the Tourism Awareness Group endeavors to develop the Meat Tourism Village through two main programs, which are : Coordinate with the Tourism Office to strengthen human resources (HR) in the tourism sector and organize annual program activities of the Meat Art Festival and cooperate with Meat Village authorities, private parties and community